2014
DOI: 10.1371/journal.pgen.1004079
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα Is Required for Long-Term Self-Renewal and Lineage Priming of Hematopoietic Stem Cells and for the Maintenance of Epigenetic Configurations in Multipotent Progenitors

Abstract: Transcription factors are key regulators of hematopoietic stem cells (HSCs) and act through their ability to bind DNA and impact on gene transcription. Their functions are interpreted in the complex landscape of chromatin, but current knowledge on how this is achieved is very limited. C/EBPα is an important transcriptional regulator of hematopoiesis, but its potential functions in HSCs have remained elusive. Here we report that C/EBPα serves to protect adult HSCs from apoptosis and to maintain their quiescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 63 publications
1
100
0
Order By: Relevance
“…Recent studies show Mecom and Cebpa as part of the top 10% of genes that exhibit decreased and increased expression, respectively, during the transition from early stage, long term HSCs to lineage-committed progenitor cells (33), and Cebpa has a documented role in maintaining hematopoietic stem cells (15,18). Together, these published data and our data indicate that the function of EVI1 in maintaining HSCs may include maintaining Cebpa mRNA levels at a low level to prevent premature myeloid maturation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show Mecom and Cebpa as part of the top 10% of genes that exhibit decreased and increased expression, respectively, during the transition from early stage, long term HSCs to lineage-committed progenitor cells (33), and Cebpa has a documented role in maintaining hematopoietic stem cells (15,18). Together, these published data and our data indicate that the function of EVI1 in maintaining HSCs may include maintaining Cebpa mRNA levels at a low level to prevent premature myeloid maturation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For reciprocal transplantation, 3 × 10 6 Ly5. Hasemann et al (2014). Microarray data were normalized by RMA (robust multiarray analysis) followed by mean one-step probe set summarization using the Partek genomics suite 6.5 followed by analysis of differential expression between experimental groups (expression fold change >1.5; P < 0.05; q < 0.22, ANOVA F-test).…”
Section: Transplantation Assaysmentioning
confidence: 99%
“…Numerous studies in mice have identified factors that support self-renewal, including C/ EBPα, c-MYB, and SATb1 (Lieu and Reddy 2009;Will et al 2013;Hasemann et al 2014). Other factors, such as DNMT3a, shown to restrict self-renewal, are equally prevalent (Challen et al 2012).…”
mentioning
confidence: 99%
“…At the HSC stage, C/EBPα acts to prime HSCs for differentiation along the myeloid lineage via DNA binding to regulatory regions of genes induced during differentiation (16). Although conditional Cebpa knockout mice do not develop disease, the loss of Cebpa in adult HSCs leads to an increased number of functional and proliferative HSCs (15,17) and loss of HSC pool maintenance in serial transplantations (16). Cebpa expression is required for AML disease initiation by the oncogene MLL-ENL but not for disease maintenance (18).…”
Section: Introductionmentioning
confidence: 99%